A Proposal of Algorithm for Automated Chromosomal Abnormality Detection - Pysarchuk, Oleksii; Mironov, Yurii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
The article considers the problem of automatic chromosome abnormalities recognition, using images of chromosomes as an input. This paper’s scope includes overview of application domain and analysis of existing solutions. A high-level algorithm for chromosome abnormalities recognition automation is proposed, and a proof-of-concept application is built on top of the algorithm.